Development of spin‐contrast‐variation neutron powder diffractometry for extracting the structure factor of hydrogen atoms. Issue 2 (3rd March 2021) - Miura, Daisuke; Kumada, Takayuki; Sekine, Yurina; Motokawa, Ryuhei; Nakagawa, Hiroshi; Oba, Yojiro; Ohhara, Takashi; Takata, Shin-ichi; Hiroi, Kosuke; Morikawa, Toshiaki; Kawamura, Yukihiko; Ohishi, Kazuki; et al.
Abstract : A spin‐contrast‐variation neutron powder diffractometry technique is developed, where the coherent scattering length of hydrogen is controlled by proton polarization. This technique extracts the hydrogen structure factor, i.e. the contribution of hydrogen atoms to a crystal's structure factor. Abstract : A spin‐contrast‐variation neutron powder diffractometry technique that extracts the structure factor of hydrogen atoms, i.e. the contribution of hydrogen atoms to a crystal's structure factor, has been developed. Crystals of l ‐glutamic acid were dispersed in a d ‐polystyrene matrix containing 4‐methacryloyloxy‐2, 2, 6, 6, ‐tetramethyl‐1‐piperidinyloxy to polarize their proton spins dynamically. The intensities of the diffraction peaks of the sample changed according to the proton polarization, and the structure factor of the hydrogen atoms was extracted from the proton‐polarization‐dependent intensities. This technique is expected to enable analyses of the structures of hydrogen‐containing materials that are difficult to determine with conventional powder diffractometry.